Large‐scale eDNA metabarcoding survey reveals marine biogeographic break and transitions over tropical north‐western Australia. Issue 10 (24th January 2021) - West, Katrina; Travers, Michael J.; Stat, Michael; Harvey, Euan S.; Richards, Zoe T.; DiBattista, Joseph D.; Newman, Stephen J.; Harry, Alastair; Skepper, Craig L.; Heydenrych, Matthew; Bunce, Michael
Abstract: Aim: Environmental DNA (eDNA) metabarcoding has demonstrated its applicability as a highly sensitive biomonitoring tool across small spatial and temporal scales in marine ecosystems. However, it has rarely been tested across large spatial scales or biogeographical barriers. Here, we scale up marine eDNA metabarcoding, test its ability to detect a major marine biogeographic break and evaluate its use as a regional biomonitoring tool in Australia. Location: North‐western Australia (NWA). Methods: We applied metabarcoding assays targeting the mitochondrial 16S rRNA and CO1 genes to 284 surface seawater eDNA samples collected from 71 mid‐shelf, inshore, coastal and nearshore estuarine sites over 700 km of the NWA coastline. Results: Metabarcoding detected a wide range of bony fish (404 taxa), elasmobranchs (44) and aquatic reptiles (5). We detected bioregional and depth differentiation within inshore bony fish communities. These findings support the presence of a marine biogeographic break, which is purported to occur in the vicinity of Cape Leveque, demarcating the border between the Kimberley and Canning bioregions. Inshore bony fish and elasmobranch communities, as well as coastal bony fish assemblages, were additionally found to differ between the South and North Kimberley regions suggesting previously unrecognized subregional differentiation amongst these taxa. The overall compositional data have been used to update distribution information for a number of endangered, elusive and data‐deficient taxa, including sawfish (family: Pristidae), northern river shark ( Glyphis garricki ) and wedgefish (genus: Rhynchobatus ). Main conclusions: eDNA metabarcoding demonstrated a high level of sensitivity that was able to discern fine‐scale patterns across the large‐scale, remote and oceanographically complex region of North‐western Australia. Importantly, this study highlights the potential of integrating broad‐scale eDNA metabarcoding alongside other baseline surveys and long‐term monitoring approaches, which are crucial for the sustainable management and conservation of marine biodiversity in this unique marine region.